Same, but is it similar? a case report - Awang, Mohd Shukrimi; Abdul Rashid, Amran; Mohd Ghalib, Razali; Che Ahmad, Aminudin; Harun, Nora (2007)
Tuberculous spondylitis may be imposable to differentiate from pyogenic vertebral osteomyelitis and other primary or metatastatic tumours based on clinical and radiographic findings. There are no specific features that are pathognomonic of tuberculous spondylitis. Common finding that arouse suspicion are rarefaction of the vertebral endplates, disc-space narrowing, anterior wedging and paravetebral mass. However, these finding are also presence in other condition such as metastases. Two patients of different groups with almost similar presentation and imaging findings and the issues affecting their clinical course are discussed. They were a 56 year old man and a 28 year old man respectively who presented with history of bilateral lower limbs weakness of grade 3 and reduced sensation from T7 and T6 respectively. MRI showed infective process with large paravertebral mass at the level of T6-8 and T4-9 respectively. In case one o the thorax and abdomen showed small lung lesion and right adrenal mass. In case two, the histopathology supported the diagnosis of TB. Both cases presented with similar complaint although from the different age group. In this region, tuberculosis is very common. However, a high index of suspicion, together with biopsy will increase the chances of correct diagnosis. It is difficult to differentiate spinal tuberculosis and spine metastasis clinically. The imaging findings are not diagnostic. A decision to get tissue biopsy increase the chances of the accurate diagnosis. Management is depending on individual patient.